2018
DOI: 10.1590/0100-6991e-20181710
|View full text |Cite
|
Sign up to set email alerts
|

In-person and telemedicine course models for disaster preparedness: a comparative analysis

Abstract: videoconferencing can be effectively used to train health professionals in disaster management, being able to provide adequate knowledge and become an important tool to distance reaching in continuing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Furthermore, TM has proven to be a vital tool in the education and training of healthcare professionals. Various studies have demonstrated how telehealth is as effective as or more effective than traditional learning methods [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TM has proven to be a vital tool in the education and training of healthcare professionals. Various studies have demonstrated how telehealth is as effective as or more effective than traditional learning methods [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…While uncertainties persist among students, the positive response in South Asian countries suggests a shared eagerness to embrace telemedicine. The dynamic landscape post-COVID-19 and the increasing importance of telemedicine in Pakistan's healthcare future underline the need for continued research and integration efforts (20,21,22).…”
Section: Exposure and Level Of Interest Discussionmentioning
confidence: 99%
“…From the point of view of firefighters, who must confront various types of disasters, elucidation of the current situation regarding firefighting related to radiation emergencies and the factors affecting timely responses to radiation disasters could inform how to improve preparation for radiation disasters. Previous studies reported the effectiveness of education and training for disaster preparedness or planning [7][8][9][10]. Furthermore, Ben Natan et al examined variables affecting nurse willingness to work at an earthquake site and reported that 'perceived self-efficacy, level of knowledge, experience and the support of a multidisciplinary staff affect nurse willingness to report to work in the event of an earthquake' [11].…”
Section: Introductionmentioning
confidence: 99%